2022
DOI: 10.1038/s41598-022-04817-8
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral dystrophy transcriptome signatures correlate with different stages of disease and are marked by different MRI biomarkers

Abstract: With several therapeutic strategies for facioscapulohumeral muscular dystrophy (FSHD) entering clinical testing, outcome measures are becoming increasingly important. Considering the spatiotemporal nature of FSHD disease activity, clinical trials would benefit from non-invasive imaging-based biomarkers that can predict FSHD-associated transcriptome changes. This study investigated two FSHD-associated transcriptome signatures (DUX4 and PAX7 signatures) in FSHD skeletal muscle biopsies, and tested their correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…By contrast, DUX4 target genes have discriminatory power limited to separating FSHD muscle from control. Van den Heuvel et al, highlighted importance of minimally invasive biomarkers for FSHD severity, focusing on use of MRI 12 . We propose a complementary approach, based on gene expression in minimally invasive blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, DUX4 target genes have discriminatory power limited to separating FSHD muscle from control. Van den Heuvel et al, highlighted importance of minimally invasive biomarkers for FSHD severity, focusing on use of MRI 12 . We propose a complementary approach, based on gene expression in minimally invasive blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, van den Heuvel et al, 2022 12 performed RNA-sequencing of FSHD and control muscle biopsies from different muscle groups. The authors identified non-overlapping roles for PAX7 and DUX4 target genes, with both biomarkers independently associated with fatty replacement of muscle but only DUX4 target gene expression associated with inflammation 12 , consistent with our prior findings 9,11 . This emphasises importance of studying biomarkers in inflamed and non-inflamed muscle separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, using an arbitrary cut-off of DUX4 target gene expression based on RNA sequencing to assign a biopsy as DUX4+ or DUX4-showed a high correlation of STIR+ signal with DUX4+ biopsies (22, 23). A similar study also showed an association between a higher expression of DUX4-target genes and STIR+ muscle and that fat fraction measures increased the sensitivity of identifying muscles with higher levels of DUX4-target gene expression (24).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, biomarker identification and validation has been a major goal of recent FSHD clinical trial workshops [16, 17]. To date, several studies have examined DUX4 target gene expression as a proxy for DUX4 activity from invasive muscle biopsies guided by MRI imaging [18-20]. However, circulating blood-based molecular biomarkers are of particular interest as they have the potential to provide rapid, objective, minimally invasive, and quantitative measurements that can be assayed repeatedly over time using typically inexpensive methods, in contrast to tissue biomarkers that require repeated muscle biopsies.…”
Section: Introductionmentioning
confidence: 99%